2017
DOI: 10.1186/s40172-017-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

Marriage markets as explanation for why heavier people work more hours

Abstract: Is BMI related to hours of work through marriage market mechanisms? We empirically explore this issue using data from the NLSY79 and NLSY97 and a number of estimation strategies (including OLS, IV, and sibling FE). Our IV estimates (with same-sex sibling's BMI as an instrument and a large set of controls including wage) suggest that a one-unit increase in BMI leads to an almost 2% increase in White married women's hours of work. However, BMI is not associated with hours of work of married men. We also find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Swiss women have the lowest average BMI (23.7) in Europe, while men’s average BMI (26.7) lies close to the average BMI for European men (WHO, 2021 ), suggesting that the norm in Switzerland is for women being within the normal weight category while it is more acceptable for men to be above. BMI has been shown to be related to the number of work hours through marriage and labor market mechanisms (Cawley, 2015 , Grossbard & Mukhopadhyay, 2017 ). Some studies have shown that hours of work are positively associated with body weight for women, i.e., that high-BMI women work more hours (Cawley, 2015 , Caliendo, & Gehrsitz, 2016 , Grossbard & Mukhopadhyay, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Swiss women have the lowest average BMI (23.7) in Europe, while men’s average BMI (26.7) lies close to the average BMI for European men (WHO, 2021 ), suggesting that the norm in Switzerland is for women being within the normal weight category while it is more acceptable for men to be above. BMI has been shown to be related to the number of work hours through marriage and labor market mechanisms (Cawley, 2015 , Grossbard & Mukhopadhyay, 2017 ). Some studies have shown that hours of work are positively associated with body weight for women, i.e., that high-BMI women work more hours (Cawley, 2015 , Caliendo, & Gehrsitz, 2016 , Grossbard & Mukhopadhyay, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMI has been shown to be related to the number of work hours through marriage and labor market mechanisms (Cawley, 2015 , Grossbard & Mukhopadhyay, 2017 ). Some studies have shown that hours of work are positively associated with body weight for women, i.e., that high-BMI women work more hours (Cawley, 2015 , Caliendo, & Gehrsitz, 2016 , Grossbard & Mukhopadhyay, 2017 ). In the light of traditional gender values, married women have shown to be more likely than married men to receive in-marriage income transfers as women are rewarded for thinness while higher body weight reduces their bargaining power in marriage, leading to lower access to their spouse’s income (Oreffice & Quintana-Domeque, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation